P-selectin, carcinoma metastasis and heparin: novel mechanistic connections with therapeutic implications - Varki,A. (2001)
Metastasis is a multistep cascade initiated when malignant cells penetrate the tissue surrounding the primary tumor and enter the bloodstream. Classic studies indicated that blood platelets form complexes around tumor cells in the circulation and facilitate metastases. In other work, the anticoagulant drug heparin diminished metastasis in murine models, as well is in preliminary human studies. However, attempts to follow up the latter observation using vitamin K antagonists failed, indicating that the primary mechanism of heparin action was unrelated to its anticoagulant properties. Other studies showed that the overexpression of sialylated fucosylated glycans in human carcinomas is associated with a poor prognosis. We have now brought all these observations together into one mechanistic explanation, which has therapeutic implications. Carcinoma cells expressing sialylated fucosylated mucins can interact with platelets, leukocytes and endothelium via the selectin family of cell adhesion molecules. The initial organ colonization of intravenously injected carcinoma cells is attenuated in P-selectin-deficient mice, in mice receiving tumor cells pretreated with O-sialoglycoprotease (to selectively remove mucins from cell surfaces), or in mice receiving a single dose of heparin prior to tumor cell injection. In each case, we found that formation of a platelet coating on cancer cells was impeded, allowing increased access of leukocytes to the tumor cells. Several weeks later, all animals showed a decrease in the extent of established metastasis, indicating a long-lasting effect of the short-term intervention. The absence of obvious synergism amongst the three treatments suggests that they all act via a common pathway. Thus, a major mechanism of heparin action in cancer may be inhibition of P-selectin-mediated platelet coating of tumor cells during the initial phase of the metastatic process. We therefore suggest that heparin use in cancer be re-explored, specifically during the time interval between initial visualization of a primary tumor until just after definitive surgical removal.